Amniotic fluid embolism: A narrative review - Frederick J Baxter (Wolters Kluwer Medknow Publications, 2023)
Amniotic fluid embolism (AFE) is a rare but deadly complication of pregnancy. First described in 1926, it remains a diagnosis of exclusion, without clear etiology or a specific test to confirm the diagnosis. Mortality remains high and neurological injury is common among survivors, although reported case fatality rates are decreasing over time. Hemodynamic instability appears to be caused by severe pulmonary vasospasm and subsequent right heart failure, followed by severe left ventricular failure. Presentation is often sudden with loss of consciousness and circulatory arrest, requiring immediate cardiopulmonary resuscitation, vasopressor and inotropic support, and endotracheal intubation. Disseminated intravascular coagulation commonly follows with severe coagulopathy and postpartum hemorrhage and may in some cases be the primary presenting feature. Management remains largely supportive, with the use of extracorporeal membrane oxygenation and inhaled pulmonary vasodilators assuming an increased role, in addition to advanced life support methods. Blood products and coagulation factor replacement are frequently required, sometimes in the form of a massive transfusion. This narrative review summarizes the past and current literature, emphasizing rapid identification of AFE and therapeutic options for its immediate management.